2022
DOI: 10.3390/land11122122
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Heritage Tourism-Led Urban Renewal in Chinese Historical and Cultural Urban Spaces: A Case Study of Datong

Abstract: Heritage tourism-led urban renewal and regeneration has recently become a critical way of creating a city brand, designing tourism destinations, and attracting property developers and investors to cities. However, current practice points to a lack of proper understanding and consideration in preserving and interpreting elements of authentic identity in the Chinese historic urban landscape. In this study, we used the ancient city of Datong, China, under urban regeneration as a case study to explore how urban hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In this study, tourism resources are categorized into internal and external tourism resources. Internal tourism resources include some localized elements of the folk sports enterprise, such as local characteristics, intangible cultural heritage, and historical sites of the location of the folk sports enterprise [ 62 ], while external tourism resources include resources from scientific research institutes, universities, and cooperating customer groups in the location of the sports enterprise. The internal tourism resource search is more concentrated on developing folk sports projects [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, tourism resources are categorized into internal and external tourism resources. Internal tourism resources include some localized elements of the folk sports enterprise, such as local characteristics, intangible cultural heritage, and historical sites of the location of the folk sports enterprise [ 62 ], while external tourism resources include resources from scientific research institutes, universities, and cooperating customer groups in the location of the sports enterprise. The internal tourism resource search is more concentrated on developing folk sports projects [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 6 illustrates the different clusters of literature, with a total of seven distinct research themes identified. The clustering of literature themes was ranked based on the citation frequency of the most cited articles in each cluster [78]. The top two clusters are as follows: Cluster #7, with characteristic keywords such as sustainable development, urban renewal, urban regeneration, and cultural heritage.…”
Section: Literature Co-citation Analysismentioning
confidence: 99%
“…Figure 6 illustrates the different clusters of literature, with a total of seven distinct research themes identified. The clustering of literature themes was ranked based on the citation frequency of the most cited articles in each cluster [78] The analysis suggests that the preservation of traditional village cultural heritage in urban renewal is an evolving concept. Co-citation analysis assists experts and scholars in identifying highly cited and influential research articles while also offering insights into the fundamental knowledge of research areas such as sustainable development, urban renewal, urban regeneration, and cultural heritage [79].…”
Section: Literature Co-citation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the relationships between urban regeneration and tourism, Judd and Fainstein [4] noticed the tendency to create "tourism bubbles" where a high number of tourist attractions are crowded together. This is particularly evident in historic city centers, where the high concentration of heritage and cultural elements [5] as well as a large part of the retail and accommodation business [6] promotes urban vitality and preserves the city's authenticity [7].…”
Section: Introductionmentioning
confidence: 99%